At the roots of attribution of human rights to migrants - Albarello, Flavia; Rubini, Monica (Frontiers in Psychology, 2022)
Introduction This study (N = 141, Mage = 20.15) aimed at deepening knowledge on the factors that can lead young adults to deny the inalienability of human rights to migrants by examining whether, under realistic and symbolic intergroup threat (versus no-threat), the denial of human rights to migrants increases. In doing so, the role of fraternalistic relative deprivation in mediating this relation was examined. Also, two potential positive factors were considered: in-depth exploration of personal identity in the educational domain and identification with the human group. Intergroup threat was expected to enhance perceived relative deprivation, thus reducing the attribution of human rights to migrants. Such relation was expected to be mediated by those factors expressing complex views of self and others (in-depth exploration of identity in the educational domain and identification with the human group). Method Realistic and symbolic threat were experimentally manipulated through a written scenario. In the no-threat condition, no scenario was presented. Results Showed significant effects of intergroup threat on the attribution of human rights to migrants, on perceived fraternalistic relative deprivation, on in-depth exploration of identity in the educational domain and identification with the human group. More specifically, intergroup realistic threat, but not symbolic threat, reduced the attribution of human rights to migrants and identification with the human group. Symbolic threat, but not realistic threat, increased the perception of fraternalistic relative deprivation, whereas both realistic and symbolic threat reduced in-depth exploration of identity in the educational domain, and identification with the human group. As shown by the sequential mediation analysis, and as expected, the effect of intergroup threat in reducing attribution of human rights to migrants was mediated by in-depth exploration of identity in the educational domain, identification with the human group, and fraternalistic relative deprivation. Implications of findings concerning the processes underlying identification with the human group and its beneficial effects in terms of humanization of a stigmatized outgroup were highlighted by stressing the intertwined nature of personal identity and social identity processes. The importance of complex views of self and others in helping to create inclusive generations of adults was also highlighted.